CAPAIAN BELAJAR KELOMPOK KOOPERATIF TIPE MAKE A MATCH DALAM MATERI GETARAN DAN GELOMBANG UNTUK SISWA SMP NEGERI 3 TONDANO - Nopani Laluas; Jeane Cornelda Rende; Patricia Mardiana Silangen (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
The core of education consists of interactions between teachers and students to help students achieve their educational goals. The purpose of this study was to determine the success of group learning processes, the success of group results and the success of individual students in cooperative learning activities of the type Make a Match. The population in this study were all class VIII.C students in SMP Negeri 3 Tondano, consisting of 32 students. Data is extracted and collected from the results of the group learning process, group results and individual results, or results before and after the vibration and wave material test. If the success of the meeting of the learning process group I is 60% for group 1 and 56% for group II. A group learning process was achieved during Meeting II, 84% for Group I and 80% for Group II. Similarly, the learning outcomes of Group I meeting for Group I and Group II achieved the same result, namely 87.5%. During meeting II the results achieved were 90% for group I and 80% for group II, and the results of the individual successes during the pre-test were 73.125% and after the test 86.25%. From this it can be concluded that there are successes in the group learning process, group learning results and individual results when using the cooperative learning model